Current surgical strategies for treating spinal tumors: Results of a questionnaire survey among members of the German Spine Society (DWG). Issue 1 (January 2020) - Disch, A.C.; Kleber, C.; Redemann, D.; Druschel, C.; Liljenqvist, U.; Schaser, K.D.; ,
Abstract: Purpose: Questionnaire survey among the members of the German Spine Society (Deutsche Wirbelsäulen-Gesellschaft, DWG) to objectify oncological infrastructure and current standard of care in spinal tumor treatment in Germany. Methods: All DWG-members were contacted via the society's e-mail and asked to respond in anonymized form to a related questionnaire. Questions were asked regarding surgical specialty, type of institution involved, numbers of spinal procedures, as well as questions on treatment for primary tumors, whether the respondent belonged to a tumor center, decision-making procedures for surgery, and the type of procedure. Results: 84 centers providing surgical treatment for spinal tumors in their departments were identified. 52.6% were carrying out more than 500 spinal procedures per year. There was a significant association (P ≤ 0.05) between the numbers of spinal surgeries, the number of treated tumor patients per year, the organisation in a tumor center and the treatment of primary tumors. 76% are part of a local tumor center for interdisciplinary decision making (i.e.surgical treatment and adjuvant therapy). 74% of the institutions stated that conventional postoperative radiotherapy is standardly administered in the case of secondary lesions, with 24% of them referring patients to external services for radiotherapy. Conclusion: In spite of often large numbers of spinal operations, the centers perform relatively small numbers of tumor operations, particularly for primary tumors. A nearly three-quarter majority of the departments are integrated into interdisciplinary tumor care. However, there is a marked number that do not belong to an interdisciplinary organisation. Further advances in multidisciplinarity and oncology training are a continuous issue to increase treatment quality in spinal tumor patients.